Outbreaks of Adenovirus-associated Respiratory Illness on 5 College Campuses in the United States, 2018–2019. (23rd April 2020) - Kujawski, Stephanie A; Lu, Xiaoyan; Schneider, Eileen; Blythe, David; Boktor, Sameh; Farrehi, Janice; Haupt, Thomas; McBride, David; Stephens, Emily; Sakthivel, Senthilkumar K; Bachaus, Brian; Waller, Kirsten; et al.
Abstract: Background: Human adenoviruses (HAdVs) are commonly associated with acute respiratory illness. HAdV outbreaks are well documented in congregate military training settings, but less is known about outbreaks on college campuses. During fall 2018 and spring 2019, 5 United States (US) colleges reported increases in HAdV-associated respiratory illness. Investigations were performed to better understand HAdV epidemiology in this setting. Methods: A case was defined as a student at one of the 5 colleges, with acute respiratory illness and laboratory-confirmed HAdV infection during October 2018–December 2018 or March–May 2019. Available respiratory specimens were typed by HAdV type-specific real-time polymerase chain reaction assays, and for a subset, whole genome sequencing was performed. We reviewed available medical records and cases were invited to complete a questionnaire, which included questions on symptom presentation, social history, and absenteeism. Results: We identified 168 HAdV cases. Median age was 19 (range, 17–22) years and 102 cases (61%) were male. Eleven cases were hospitalized, 10 with pneumonia; 2 cases died. Among questionnaire respondents, 80% (75/94) missed ≥ 1 day of class because of their illness. Among those with a type identified (79%), HAdV types 4 and 7 were equally detected, with frequency of each varying by site. Genome types 4a1 and 7d were identified, respectively, by whole genome sequence analysis. Conclusions: HAdV respiratory illness was associated with substantial morbidity and missed class time among young, generally healthy adults on 5 US college campuses. HAdVs should be considered a cause of respiratory illness outbreaks in congregate settings such as college campuses. Abstract : Outbreaks of adenovirus types 4 and 7 among students at colleges during 2018–2019 were associated with severe acute respiratory illness and considerable missed class time. Adenovirus should be considered as a possible cause of respiratory illness among college students.